Male depression: a study about hospital admissions in the center-west region of Minas Gerais - Ana Gabriela Silva; Juliana de Jesus Silva; Hélida Silva Salomé; Richardson Miranda Machado (Universidade Federal de Santa Maria, 2012)
Objective: to identify socio-demographic and clinical characteristics of the male genre suffering by Depressive Disorder. Method: retrospective and exploratory study conducted at the Clinical St. Benedict Menni, consisting of 399 patients. Results: the predominant features were age 41-50 years with 109 (27.3%); hospitalized by family own with 164 (41.1%) and length of stay exceeding 30 days, with 101 (25,3%). The largest type of liberation of the hospital was classified as medical liberation, with 330 (82.7%). The first hospitalization prevailed, with 350 (87.7%). The main funder of hospitalizations were in the Public Health System, with 321 (80.4%) admissions. Conclusion: the fact that men report less depressive symptoms contributes to the fake idea that Depressive Disorders affect less the male genre. In the last years, the number of admitted men through depression raised. Therefore health of these must receive attention